Search for new phenomena in different-flavour high-mass dilepton final states in pp collisions at √s = 13 TeV with the ATLAS detector - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; et al. (The European physical journal. C, Particles and fields, 2016)
A search is performed for a heavy particle decay-ing into different flavour dilepton pairs (eμ, eτ or μτ), using 3.2 fb−1 of proton–proton collision data at √s=13 TeV collected in 2015 by the ATLAS detector at the Large Hadron Collider. No excess over the Standard Model prediction isobserved. Limits at the 95 % credibility level are set on themass of a Z′ boson with lepton-flavour-violating couplings at 3.0, 2.7 and 2.6 TeV, and on the mass of a supersymmetric τ sneutrino with R-parity-violating couplings at 2.3, 2.2 and 1.9 TeV, for eμ, eτ and μτ final states, respectively. The results are also interpreted as limits on the threshold massfor quantum black hole production
Im Titel steht der Buchstabe "s" unter dem Wurzelsymbol
*ATLAS Collaboration: M. Aaboud, C.F. Anders, V. Andrei, C. Antel, A.E. Baas, O. Brandt, J.J. Djuvsland, M. Dunford, D.E. Ferreira de Lima, M.P. Geisler, M. Giulini, P. Hanke, J. Jongmanns, E.-E. Kluge, M. Kolb, M. Kretz, A. Kugel, V.S. Lang, M. Lisovyi, K. Meier, H. Meyer zu Theenhausen, D.I. Narrias Villar, M. Sahinsoy, S. Schaetzel, V. Scharf, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, R. Stamen, P. Starovoitov, S. Suchek, M. Wessels [und 2830 weitere Personen]
Gesehen am 08.04.2020